Reconstructing two millennia of copper and silver metallurgy in the Lake Titicaca region (Bolivia/Peru) using trace metals and lead isotopic composition. (June 2021) - Guédron, S.; Tolu, J.; Delaere, C.; Sabatier, P.; Barre, J.; Heredia, C.; Brisset, E.; Campillo, S.; Bindler, R.; Fritz, S.C.; Baker, P.A.; Amouroux, D.
Graphical abstract: Highlights: We studied copper (Cu) and silver (Ag) deposition in lake sediment. Two sediment cores from Lake Titicaca provide a ∼2400 years history of metallurgy. Pb isotopic fingerprinting allowed identifying ore sources in the central Andes. Tiwanaku copper mining was performed by smelting of local ores. Late intermediate, Inca and Colonial mining was performed in the Potosi region. Abstract: Copper, silver, and gold exploitation has been a foundation of economic and socio-cultural development of Andean societies, at least for the last three millennia. The main centers of pre-colonial metallurgy are well-known from archeological artifacts, but temporal gaps inherent in this record handicap a finer understanding of the modalities of ore exploitation by succeeding civilizations. A continuous record over time of trace metals emitted during ore smelting operations make lake sediments excellent candidates to fill those gaps. Two millennia of metallurgy were reconstructed from atmospherically derived metals together with lead (Pb) isotope ratios in two dated sediment cores from Lake Titicaca. The first evidence for metallurgy is found during the apogee of the Tiwanaku state (AD 800–1150), with a higher copper (Cu) accumulation that can be attributed to the smelting of local Cu ores, based on Pb isotopic fingerprinting. During the Late Intermediate Period (AD 1150–1450), recorded peaks in metal deposition that persisted for ∼ twenty years show that mining activities were intensive but discontinuous. Pb isotope ratios suggest diversified extractive activities, mainly located in the southern part of the central Altiplano. Finally, the most intense mining epoch began during the Inca Empire (ca. AD 1500) and lasted until the end of the Colonial Period (AD 1830), with unprecedented metal deposition over this interval. Pb isotope fingerprinting shows that mining operations occurred mainly in the Lake Titicaca and Potosi areas and were responsible for metal emissions recorded in the entire Altiplano, as evidenced by other studies.